Narrative transportation cues in direct-to-consumer advertisements: an analysis of visual content - Montgomery, Stephanie Lynn (Frontiers in Communication, 2025)
The pharmaceutical industry uses Direct-to-consumer advertisements (DTCAs) to persuade consumers: they communicate stories about health and are regulated closely by the Food and Drug Administration (FDA). Advertisers are required to balance positive outcomes with the risks and side effects associated with the medication promoted. In 2023, the FDA added that the major statement must be presented in a clear, conspicuous, and neutral manner. Visual narratives captivate viewers and are highly persuasive, but few studies have examined their cues closely. Transportation, a component of Narrative Theory, was used in this research to analyze the visual stories in 49 DTCAs. The ads aired on the top 10 broadcast network and cable television programs at the end of the 2016 and 2018 seasons. The following transportation cues were identified and analyzed: novelty; vivid sensory information, and visual-verbal redundancy (VVR). The majority of the ads contain multiple exemplars and stories that culminate in a unifying positive message about the effects of taking the medicine advertised, and imply its role as a catalyst for improved health. The transportation cues studied indicate that these ads are engaging in novel ways and use strategies that blur the lines between reality and fiction. In addition, VVR communicates such positive information frequently. Understanding the visual representations and transportation cues increases DTCA literacy, contributes to ongoing research by the FDA and policy development, and informs consumers and healthcare practitioners about the ways in which pharmaceutical companies present their products to the public.